1999
DOI: 10.1073/pnas.96.20.10984
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the human βII-tryptase tetramer: Fo(u)r better or worse

Abstract: Tryptases, the predominant serine proteinases of human mast cells, have recently been implicated as mediators in the pathogenesis of allergic and inf lammatory conditions, most notably asthma. Their distinguishing features, their activity as a heparin-stabilized tetramer and resistance to most proteinaceous inhibitors, are perfectly explained by the 3-Å crystal structure of human ␤II-tryptase in complex with 4-amidinophenylpyruvic acid. The tetramer consists of four quasiequivalent monomers arranged in a f lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 48 publications
3
78
0
Order By: Relevance
“…Due to this organization, tryptase is resistant to all known macromolecular protease inhibitors found in mammals (23). The enzyme is thereby well suited for carrying out proteolytic processes in the cellular environment, unhindered by the multitude of protease inhibitors of serpin type that are abundant within the cytosol and also in the nucleus (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this organization, tryptase is resistant to all known macromolecular protease inhibitors found in mammals (23). The enzyme is thereby well suited for carrying out proteolytic processes in the cellular environment, unhindered by the multitude of protease inhibitors of serpin type that are abundant within the cytosol and also in the nucleus (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Further proof that the compounds present in the monomer position actually corresponded to active monomers (and not to tetramers that had been assembled after the chromatography step) came from inhibition studies in which BPTI was shown to inhibit tryptase in the monomer (but not tetramer) fraction. Resistance to macromolecular protease inhibitors is a classical feature of the mast cell tryptase tetramer (9) and is explained by its molecular organization, where the active sites that are located in the central pore are inaccessible to large protease inhibitors due to steric reasons (6,7). The access to the active site in an active monomer would obviously be less restricted, which would facilitate interaction with macromolecular protease inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…24 Crystallography studies have shown that this enzymatically active ␤-tryptase is a ringlike tetramer structure of approximately 130 kDa, with the active sites of the monomers facing the central pore. 37,38 Localization of these active sites in the central pore limits accessibility of these sites to macromolecular substrates and inhibitors. The only naturally occurring tryptase inhibitor identified thus far is the Kazal-type leech-derived tryptase inhibitor (LDTI), which is smaller than other inhibitors.…”
Section: Discussionmentioning
confidence: 99%